MODEL PEMBERDAYAAN MASYARAKAT NELAYANDALAM PENGENTASAN KEMISKINAN DI DUSUN PULAU CEMPEDAK KECAMATAN KENDAWANGANKABUPATEN KETAPANG - B61110062, HERONIMUS TANAM (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRAK This research entitles "Enableness Model of Fisherman Public in Eradicate extreme poverty(Pengentasan Kemiskinan) in Pulau Cempedak Village at Kendawangan District Ketapang Regency, by Heronimus Tanam the year 2013, be case study research, aim to analyse, compiles and merangcang model, strategy, policy for the agenda of enableness of fisherman public for the agenda of pengentasan poorness in Pulau Cempedak Village at Kendawangan District Ketapang Regency . Form of research is descriptive research, with model/analyzed applied is SWOT method namely with identifying strength (strength), weakness ( weakness), opportunity ( opportunity) and threat ( treath). The result of research and survey and identification of internal factor and eksternal is known condition of effort for fishery in Cempedak's Island of Kendawangan's district at Ketapang Regency lies on Third Quadrant (turn around) so model or empowerment pattern in point is with utilize opportunity to settle weakness. Recommended common strategy is 1) Penyediaan is medium and prasarana is fishery arrest, 2) Constructions on islandic and Family and resident, 3) Increase education and fisherman society healths, 4) Pendampingan and counsellings to fishermen, 5) effort Development and capital application/investments for fisherman hole in the wall, 6) medium Development and prasarana is conducting fisheries, 7) common Medium Developments. Meanwhile special strategy is with exploit the nationals programs as PUMP, and really lents fund to get moving of on duty of Ketapang Regency fishery. Key word: Fisherman, Poorness, Beggary, Empowerment, Strength, Weakness, Opportunity, Threat.